Hardcore, punk, and other junk : aggressive sounds in contemporary music - Abbey, Eric James, 1976-; Helb, Colin; Ware, Evan; Ahern, Sean; Elovaara, Mika; Erbe, Marcus; Varas Díaz, Nelson; Rivera-Segarra, Eliut; Hagan, Ross; Cogan, Brian, 1967-; Fellezs, Kevin (Lexington Books, 2014)
Hardcore, Punk, and Other Junk: Aggressive Sounds in Contemporary Music, edited by Eric James Abbey and Colin Helb, is a collection of writings on music that is considered aggressive throughout the world. This collection reflects the importance of aggressive music within our society and how this music effects and informs contemporary issues.